XPS study of Cr segregation in a martensitic stainless steel. (21st March 2020) - Bolli, Eleonora; Fava, Alessandra; Kaciulis, Saulius; Mezzi, Alessio; Montanari, Roberto; Varone, Alessandra
Abstract : Cr martensitic steels are promising materials for structural applications in future nuclear fusion reactors. Because the embrittlement after tempering treatments can be a serious problem, the fracture mode of a steel with 10.5 wt% of Cr treated at 700°C for 18 h has been investigated through Charpy tests in the temperature range from −100°C to +150°C. X‐ray photoelectron spectroscopy (XPS) analyses carried out on the fracture surfaces evidenced the segregation of Cr in both ductile and brittle (quasicleavage) fields. The unexpected result indicates that Cr segregation weakens the atomic bonds; thus, the fracture path in both the cases corresponds to the zones with higher Cr content.